المماثلة الصوتية والإدغام في الصوتيات العربية -المصطلح والمفهوم بين القدماء والمحدثين - Mohamed Oulddali (Al-Lisaniyyat)
Assimilation and gemination are among the combinatorial phonetic terms which have experienced some conceptual confusion among Arabic phoneticians (ancient and contemporary). This research aims to define, in a precise manner, the conceptual components of the two terms in order to draw the boundaries between them. Assimilation and gemination have been found to be non-functional phonetic phenomena, used to facilitate pronunciation. However, gemination is not considered as a phenomenon of assimilation, but rather a type of dissimilation. This is why it must be distinguished by naming it with the foreign term: “Gemination”. Thus, gemination is not an assimilation by the insertion or fusion of one consonant into another during pronunciation, but rather the pronunciation of two consonants at the same time, ignoring the vowel between them.